Gameplay mechanics : game development essentials. - Dunniway, Troy, ....-; Novak, Jeannie, 1966- (New York : Delmar Cengage Learning, 2008)
This book will introduce both aspiring and professional designers to the exciting and fast-paced world of gameplay system design. Designing successful next-generation console games has become an increasingly complicated business as gamers are demanding more features and more complexity in the games that they play. More than ever, game designers are faced with the challenge of balancing consumer expectations with strict marketing requirements, schedule deadlines and budget limitations. With a hands-on, practical approach, Game Development Essentials: Gameplay Mechanics will teach readers how to approach game design in an efficient way that will meet the objectives of the target audience, as well as the businesses that fund their development, by approaching game design as an interaction of various systems, instead of individual, unique but unrelated features. With an end goal of creating exciting, dynamic, and engaging games, this book will help readers navigate the options and make intelligent choices in their game design.